THE PORTRAYAL OF ALTRUISTIC BEHAVIOR IN THREE SELECTED PICTURE BOOKS - Prayuana, Ratu; Egilistiani, Rahmita; Fatimah, Citra (BASIS (Bahasa dan Sastra Inggris), 2025)
This study aims to analyze altruistic behavior represented in three selected picture books. All three picture books have a common thread in building children's awareness of helping others and entering into the discussion of altruistic behavior. The objects of this study are three picture books entitled Little Miss Mary and the Big Monster Makeover by G.G. Toropov and Cleone Cassidy (2008), Harold Loves His Woolly Hat by Vern Kousky (2018), and My Brother's Wheelchair by Salil Chaturvedi (2019). The researchers conducted qualitative research by examining the image of pictures and the texts available in the picture books. The data were collected through close reading and content analysis, focusing on both textual and visual narratives. According to Ary et al. (2010), close reading in literature involves examining the formal elements. In doing so, the researchers use the theory of Ricard (2015) as the basis of the results of the analysis, which then finds this altruistic behavior related to the discussion. By observing the plot in the story and exploring the implicit message of the author in fostering social awareness in children as readers, these three picture books instill understanding to help others without asking for reciprocity and are only based on a simple desire oneself to help others selflessly.